2015
DOI: 10.1016/j.scriptamat.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Determination of strain rate in Friction Stir Welding by three-dimensional visualization of material flow using X-ray radiography

Abstract: Recrystallization, which is mainly caused by the induced strain, is one of the most important factors of Friction Stir Welding. In this study, strain and strain rate are directly obtained by the change in the material flow velocity which is observed by three-dimensional visualization of the material flow. The grain size of the pure aluminum in the stir zone estimated by the Zener-Hollomon parameter using the obtained strain rate shows good agreement with that observed by Electron Back-Scatter Diffraction mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 24 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…The particles were subjected to severe plastic deformation during FSP, which resulted in an L/W of 12. However, the strain rate in the flow zone was low due to the constant angular velocity of the material flow [21]. So, spherical 34CrNiMo6 particles and slim particles both existed in the specimens.…”
Section: Resultsmentioning
confidence: 98%
“…The particles were subjected to severe plastic deformation during FSP, which resulted in an L/W of 12. However, the strain rate in the flow zone was low due to the constant angular velocity of the material flow [21]. So, spherical 34CrNiMo6 particles and slim particles both existed in the specimens.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, the effect of the laser-preheating on the material flow during the FSW was investigated by in-situ observations using X-ray radiography. [16][17][18]…”
Section: Friction Stir Welding Of Medium Carbon Steel With Laser-prehmentioning
confidence: 99%
“…In this study, the material flow during the conventional FSW and laser-preheating FSW was observed by two pairs of high brightness X-ray inspection apparatuses consisting of X-ray generators and high responsive image intensifiers. [16][17][18] The perspective images observed from two different direction were recorded by high speed cameras. The appearance and schematic illustration of high brightness X-ray inspection apparatuses were shown in Figs.…”
Section: In Situ Observation Of Materials Flow Behaviormentioning
confidence: 99%
“…[14] It is interesting to note that the material may experience several rotations around the tool before its final deposition in the stir zone. [15,16] The combination of the rotation and translation motions of the tool gives rise to a characteristic asymmetry of FSW: the advancing side (AS), where the direction of the tool rotation is the same as that of the tool translation, and the retreating side (RS), where they are opposite. The material flow on the AS is believed to be relatively stagnant and may result in a wormhole defect, [15,[17][18][19][20] but the nature of this undesirable effect is not completely clear.…”
Section: Introductionmentioning
confidence: 99%